Halloysite Nanotube-Based Delivery of Pyrazolo[3,4-d]pyrimidine Derivatives for Prostate and Bladder Cancer Treatment - Marina Massaro; Rebecca Ciani; Giancarlo Grossi; Gianfranco Cavallaro; Raquel de Melo Barbosa; Marta Falesiedi; Cosimo G. Fortuna; Anna Carbone; Silvia Schenone; Rita Sánchez-Espejo; César Viseras; Riccardo Vago; et al. (MDPI AG, 2024)
Background/Objectives: The development of therapies targeting unregulated Src signaling through selective kinase inhibition using small-molecule inhibitors presents a significant challenge for the scientific community. Among these inhibitors, pyrazolo[3,4-d]pyrimidine heterocycles have emerged as potent agents; however, their clinical application is hindered by low solubility in water. To overcome this limitation, some carrier systems, such as halloysite nanotubes (HNTs), can be used. Methods: Herein, we report the development of HNT-based nanomaterials as carriers for pyrazolo[3,4-d]pyrimidine molecules. To achieve this objective, the clay was modified by two different approaches: supramolecular loading into the HNT lumen and covalent grafting onto the HNT external surface. The resulting nanomaterials were extensively characterized, and their morphology was imaged by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). In addition, the kinetic release of the molecules supramolecularly loaded into the HNTs was also evaluated. QSAR studies were conducted to elucidate the physicochemical and pharmacokinetic properties of these inhibitors, and structure-based virtual screening (SBVS) was performed to analyze their binding poses in protein kinases implicated in cancer. Results: The characterization methods demonstrate successful encapsulation of the drugs and the release properties under physiological conditions. Furthermore, QSAR studies and SBVS provide valuable insights into the physicochemical, pharmacokinetic, and binding properties of these inhibitors, reinforcing their potential efficacy. Conclusions: The cytotoxicity of these halloysite-based nanomaterials, and of pure molecules for comparison, was tested on RT112, UMUC3, and PC3 cancer cell lines, demonstrating their potential as effective agents for prostate and bladder cancer treatment.